Impact of preoperative SYNTAX Scores on short-term outcome following coronary artery bypass grafting surgery in the patients with multi-vessels coronary artery disease - Ramadan, Bassem Adel (Egypt Heart J, 2020)
BACKGROUND: SYNTAX Scores I (SSI) assesses the complexity of CAD; SYNTAX Score II (SSII) uses both SSI and other clinical variables, in estimation of 4 years mortality following both coronary artery bypass grafting surgery (CABG) and percutaneous coronary intervention (PCI) and gives recommendations for the best revascularization strategy in a specific patient. Our aim is to investigate the impact of both SYNTAX Scores on short-term outcome following CABG. RESULTS: Prospectively, we studied 150 patients with multi-vessels coronary artery disease, referred to perform, elective primary isolated CABG. All cases performed on pump CABG with aortic cross clamping, then followed up for 90 days postoperatively, for onset of mortality from all causes, myocardial infarction (MI), stroke, mediastinitis, and need for renal replacement therapy (RRT). SSI showed a statistically significant association with in-hospital and 90 days mortality, MI, and mediastinitis (P = < 0.001, 0.015, 0.045 respectively); SSII showed a statistically significant association with in-hospital mortality and 90 days mortality and need for renal replacement therapy (P = 0.007, 0.043, 0.012 respectively); SSI is independent risk factor for overall mortality (OR 1.192, 95% CI 1.018–1.396) (P = 0.029) and MI (OR 1.182, 95% CI 1.016–1.375). CONCLUSIONS: SYNTAX Scores are good predictors of short-term outcome after CABG; increased SSI was associated with increased mortalities (in-hospital and total 90 days), MI and mediastinitis, increased SSII associated with increased mortalities (in-hospital and total 90 days), and need for RRT; SSI is independent risk factor for mortality and MI.